Changes in Dosing and Dose Timing of D-Cycloserine Explain Its Apparent Declining Efficacy for Augmenting Exposure Therapy for Anxiety-related Disorders: An Individual Participant-data Meta-analysis. (December 2019) - Rosenfield, David; Smits, Jasper A.J.; Hofmann, Stefan G.; Mataix-Cols, David; de la Cruz, Lorena Fernández; Andersson, Erik; Rück, Christian; Monzani, Benedetta; Pérez-Vigil, Ana; Frumento, Paolo; Davis, Michael; de Kleine, Rianne A.; et al.
Highlights: The apparent effectiveness of d-cycloserine for anxiety disorders has declined over time This "decline effect" may be due to how d-cycloserine (DCS) has been administered Our individual participant data meta-analysis included 1047 patients in 21 trials Number and timing of DCS doses, and severity, appears to account for this decline Optimal number and timing of DCS doses may increase its effectiveness by 50% ABSTRACT: The apparent efficacy of d-cycloserine (DCS) for enhancing exposure treatment for anxiety disorders appears to have declined over the past 14 years. We examined whether variations in how DCS has been administered can account for this "declining effect". We also investigated the association between DCS administration characteristics and treatment outcome to find optimal dosing parameters. We conducted a secondary analysis of individual participant data obtained from 1047 participants in 21 studies testing the efficacy of DCS-augmented exposure treatments. Different outcome measures in different studies were harmonized to a 0-100 scale. Intent-to-treat analyses showed that, in participants randomized to DCS augmentation (n = 523), fewer DCS doses, later timing of DCS dose, and lower baseline severity appear to account for this decline effect. More DCS doses were related to better outcomes, but this advantage leveled-off at nine doses. Administering DCS more than 60 minutes before exposures was also related to better outcomes. These predictors were not significant in the placebo arm (n = 521). Results suggested that optimal DCS administration could increase pre-to-follow-up DCS effect size by 50%. In conclusion, the apparent declining effectiveness of DCS over time may be accounted for by how it has been administered. Optimal DCS administration may substantially improve outcomes. Registration: The analysis plan for this manuscript was registered on Open Science Framework (https://osf.io/c39p8/ ).